The urgency of financial literacy and inclusion in managing finances of STMIK Kaputama students - Selfira Selfira (International Journal of Applied Finance and Business Studies, 2025)
This research investigates the impact of financial inclusion and financial literacy on financial management through the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The analysis involved evaluating the reliability, validity, and structure of the model. Results from the reliability tests indicated that all constructs fulfilled the necessary criteria, with composite reliability values surpassing 0.84 and Cronbach’s alpha confirming sufficient internal consistency. Convergent validity was supported by AVE values exceeding 0.65, while discriminant validity yielded mixed outcomes. The Fornell-Larcker Criterion revealed a potential overlap between financial inclusion and financial literacy constructs. The path coefficient analysis demonstrated that financial inclusion had a significant and positive influence on financial management (β = 0.394, p = 0.017), whereas financial literacy did not produce a statistically significant effect (β = 0.083, p = 0.561). These results imply that access to financial services has a more immediate impact on effective financial management than financial knowledge alone. The study emphasizes the importance of practically applying financial literacy to strengthen its effectiveness.